What does European institutional integration tell us about trade integration? - Francesco Paolo Mongelli; Ettore Dorrucci; Itai Agur (European Central Bank (ECB), 2005)
The start of the European Economic and Monetary Union (EMU) has spurred a new interest in the debate on the effects of monetary unions on regional economic integration. This literature either investigates past episodes of monetary unions or attempts to gauge any effect with a few years of EMU data. This paper takes instead a more general perspective - it investigates the link between economic integration and the overall institutional process of regional integration in Europe – of which monetary integration was only one step – over the last 50 years. We look mainly at two dimensions - European institutional integration – whose main steps were the customs union in 1968, the single market in 1993 and the single currency in 1999 – and intra-European trade. We pay special attention to the successive EU enlargements which took place in 1973, 1981, 1986, and 1995. Different facets of openness and trade linkages are presented. After looking at some descriptive links between institutional and trade integration, the paper uses some causality tests to assess the direction of causality and magnitude of impact. The evidence provided is consistent with the idea that the interaction between regional institutional and trade integration before monetary union matters. Such interaction runs in both directions, although the link from institutional to trade integration dominates. Many open questions remain, however.
Keywords: E42; F15; F33; F41; 330; Optimum Currency Area; Economic and Monetary Integration and EMU.; Eurozone; Regionale Wirtschaftsintegration; EU-Staaten